The Effectiveness of Emotional Schema Therapy on Neuroticism and the Life Style of Cardiovascular Patients - Z Khodadad Hatkeh Poshti (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Neuroticism and extroversion have a high and positive relationship with psychological problems such as anxiety and depression. Since cardiovascular diseases are also considered as psychotic that can be reduced by modifying lifestyles and changing high risk behaviors this study was conducted to compare the effectiveness of emotional schema therapy on neuroticism and lifestyle of cardiovascular patients. METHODS: This cross-sectional study was performed on 30 patients with cardiovascular disease referred to Rouhani Hospital in Babol who were randomly divided into two groups of emotional schema therapy and control. The emotional schema therapy protocol was performed during 12 weekly sessions of 2 hours. Using NEO-FFI (score 12-60) and Health Promoting Lifestyle (HPLPII) questionnaires (score 48-192), before the intervention, after the intervention and one month later, the two groups were evaluated and compared. FINDINGS: There was no significant difference between the two groups in terms of age and sex. The mean scores of neuroticism before and after the intervention in the control group were 38.93±7.31 and 37.80±4.63, respectively, and in the emotional schema therapy group were 37.73±6.94 and 32.53±6.75, respectively. The mean score of promoter lifestyle in emotional schema therapy group before and after the intervention was 113.13±28.25 and 138±32.27, respectively (p<0.05). Implementation of emotional schema therapy had a significant effect on Neuroticism (6.95, 0.014 and 0.205) and lifestyle (11.67, 0.002 and 0.302) and led to the reduction of Neuroticism and the promotion of lifestyle. CONCLUSION: The results of this study showed that emotional schema therapy can be an effective intervention in reducing neuroticism and promoting lifestyle in cardiovascular patients.